A Rapid DMeyer-CWT Method Application to the Spectrophotometric Data for the Quantification of Losartan Potassium and Hydrochlorothiazide in a Binary Mixture - Erdal Dinç; Özgür Üstündağ (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This paper outlines a precise, swift, and convenient spectrophotometric method based on the continuous wavelet transform methodology for the estimation of losartan potassium and hydrochlorothiazide in tablets. The continuous wavelet transform method is based on the use of DMeyer (DMEY-CWT). When the original UV spectra of losartan potassium and hydrochlorothiazide are studied, it is clear that their spectra closely overlap. The analysis was completed successfully without any pre-separation using the created DMEY-CWT approach. The calibration equations for losartan potassium measurement and hydrochlorothiazide determination were obtained at 257.6 nm and 268.4 nm for losartan potassium, 250.1 nm and 263.8 nm for hydrochlorothiazide. The developed approaches were evaluated for their validity and practicality.